Intellectual Capital: A Strategic Pattern Of Improving Organizational Performance - Jalaludin, Ega (LPPM Universitas Bina Bangsa, 2021)
Industrial Era 4.0 forces every company to have a strategic pattern in improving organizational performance. The industrial revolution has changed the way humans work manually towards automation or digitization by machines. Thus, innovation and human knowledge are the key to the birth of an increasingly sophisticated industry to meet human needs themselves. This study discusses the intellectual capital variables owned by human resources in an organization. The type of research used is descriptive qualitative research because it is sourced from relevant journals. The research objects in this study are journals and other scientific articles that discuss intellectual capital and its impact on improving organizational performance. This research is expected to reveal more clearly how intellectual capital can significantly enhance organizational performance